2021
DOI: 10.1111/jpy.13153
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritable Characteristics of Monoecy and Parthenogenesis Provide A Means for Establishing A Doubled Haploid Population in the Economically Important Brown Alga Undariapinnatifida (Laminariales, Alariaceae)

Abstract: Monoecy and parthenogenesis exist in certain male and female gametophytes of the brown alga Undaria pinnatifida. The inheritance of these traits is not known. In this study, we made a cross between a male and a female gametophyte clone which could exhibit monoecy and parthenogenesis phenotypes, respectively, and obtained their next‐generation gametophyte offspring. We found that under conditions suitable for gametogenesis, all of the male offspring (n = 100) exhibited monoecy phenotype and all of the female of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…They are determined to be haploid by flow cytometry analysis, different from the diploid gametophyte derived from tissue culture of the sporophyte thalli ( Zhang et al, 2007 ; Shan et al, 2020b ). Microsatellite analysis confirmed that hybrid sporophytes could be obtained when the monoicous gametophyte was crossed with another male gametophyte, which indicates the eggs discharged by the monoicous gametophyte can really be fertilized by sperm, and thus they have the same sexual function as those discharged by the female gametophytes ( Shan et al, 2021 ). They can also self-breed to give rise to doubled haploid (DH) sporophytes, albeit the fertilization rate of the eggs during selfing is much lower than during outcrossing.…”
Section: Life Historymentioning
confidence: 81%
See 4 more Smart Citations
“…They are determined to be haploid by flow cytometry analysis, different from the diploid gametophyte derived from tissue culture of the sporophyte thalli ( Zhang et al, 2007 ; Shan et al, 2020b ). Microsatellite analysis confirmed that hybrid sporophytes could be obtained when the monoicous gametophyte was crossed with another male gametophyte, which indicates the eggs discharged by the monoicous gametophyte can really be fertilized by sperm, and thus they have the same sexual function as those discharged by the female gametophytes ( Shan et al, 2021 ). They can also self-breed to give rise to doubled haploid (DH) sporophytes, albeit the fertilization rate of the eggs during selfing is much lower than during outcrossing.…”
Section: Life Historymentioning
confidence: 81%
“…It may be partly tackled by using the DH sporophytes resulting from monoicous selfing and parthenogenesis of certain paternal and maternal gametophyte lines ( Figure 1 ). Monoicy phenotype has been shown to be more common than expected in cultivated strains ( Li et al, 2014 ; Shan et al, 2021 ). The fecundity of mature DH sporophytes is high, being able to release millions of spores with the same genotype as that of the corresponding parental gametophyte ( Shan et al, 2013 ; Shan et al, 2021 ).…”
Section: Prospects On Cultivar Breedingmentioning
confidence: 97%
See 3 more Smart Citations